Comparison of the swimming start performance between individual and relay freestyle races - Qiu, X.; Calvo, A. L.; De La Fuente, B.; Veiga, S. (ISBS Proceedings Archive (Michigan), 2020)
The aim of the present study was to compare the swimming start performances between individual and relay events in freestyle races. Competitors who took part in both the individual 100m freestyle and the 4×100m freestyle relay races during the LEN 2017 European Junior Championships were analysed in the present study. The results indicated that swimmers performed 6.92% faster 15m start time in relay race versus the individual freestyle race and the difference seemed to be due to the longer reaction time from the race beginning. Coaches and swimmers would be suggested to try to optimize their relay starting performance in order to take more benefit on flight, underwater and swimming phases compare to individual start.